2017
DOI: 10.29252/ijrm.15.1.11
|View full text |Cite
|
Sign up to set email alerts
|

The study of waiting time to first pregnancy in the south of Iran: A parametric frailty model approach

Abstract: Background: Time to first pregnancy (TTFP) has never been studied in an Iranian setting. Lifestyle, occupational and environmental factors have been suggested to affect the female reproduction. Objective: This study was conducted to measure TTFP in the south of Iran and survey the effects of several similar factors on TTFP by frailty models. Materials and Methods:The data on TTFP were available for 882 women who were randomly selected from the rural population (the south of Iran). Only the first and the planne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Bangladeshi (1) and results elsewhere (3,4,7,14,19,21,22,26,(31)(32)(33)(34)(35)(41)(42)(43). In particular, ensuring those adolescent girls to receive at least a secondary level of education is the optimal way of delaying childbirth (53,58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bangladeshi (1) and results elsewhere (3,4,7,14,19,21,22,26,(31)(32)(33)(34)(35)(41)(42)(43). In particular, ensuring those adolescent girls to receive at least a secondary level of education is the optimal way of delaying childbirth (53,58).…”
Section: Discussionmentioning
confidence: 99%
“…Those who gave rst birth at 30 years and above group were 33% at higher risk of mortality compared to those who gave rst birth in the age group 20-24 years in Ohsaki Japan (16). The impacts of urbanization and modernization postponed the age at rst birth in the later age in the developed world (9,(20)(21)(22).…”
mentioning
confidence: 99%
“…As many studies showed that the probability of early age at first birth is higher in women with no or lower level education compared to women at a higher educational level (1,5,31,33,36,37,(41)(42)(43)6,9,14,17,20,24,25,30). Most of the studies revealed that having poor and middle wealth index status was identified as the risk of age at first birth in early age (24,(30)(31)(32)(35)(36)(37)41,44).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies revealed that having poor and middle wealth index status was identified as the risk of age at first birth in early age (24,(30)(31)(32)(35)(36)(37)41,44). (5,6,(33)(34)(35)(36)(37)(38)9,14,17,20,21,25,30,31). The majority works of the literature revealed that the use of any contraception delay age at first birth (5,8,9,20,30,31,34,39,40) On the other hand, advanced maternal age (> 30 years) at first birth is associated with an increased risk of fetal loss, chromosomal anomalies, multiple pregnancies, hypertension, diabetes mellitus, preterm birth, low birth weight, breast cancer and maternal mortality (16,22,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation